Development of Local Wisdom-Based Learning Videos for Elementary School Students - Rahimi, Elvia; Nurdin, Syahidan (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to produce relevant and effective Indonesian local wisdom-based learning videos for elementary school students. The learning videos were designed based on observations, interviews with teachers, and needs analysis from a fourth-grade student questionnaire. This study used the 4D model (Define, Design, Develop, Disseminate). In the define stage, students' need for interactive and contextual media was identified. In the design stage, learning videos were designed using the Canva application to present engaging and relevant material. The develop stage involved validation by media experts, material experts, and linguists, followed by revisions to refine the product. In addition, the video's practicality was assessed by the class teacher to ensure its suitability for learning. The results showed that this learning video had a very high level of feasibility, with an average score from media experts of 93.3%, material experts 88.3%, and linguists 80%. The practicality test by the fourth-grade teacher showed a score of 99%. The overall average from the validator and practicality test was 90.15%, which is categorized as "Very Feasible".